Recent Advances of Optical Biosensors in Veterinary Medicine: Moving Towards the Point of Care Applications - Amin, Niloufar; Almasi, Ameneh; Ozer, Tugba; Henry, Charles S.; Hosseinzadeh, Leila; Keshavarzi, Zahra (BENTHAM SCIENCE PUBL LTD, 2023)
While food safety issues are attracting public concern due to their detrimental effects on human health, monitoring livestock health is urgently needed to diagnose animal diseases at an early stage by applying proper treatments, controlling, and preventing outbreaks, particularly in resource-limited countries. In addition, unhealthy farms are not only a threat to livestock but also to human lives. The available diagnostic techniques for the detection of key health threats within both the food and livestock sectors require labor-intensive and time-consuming experimental procedures and sophisticated and expensive instruments. To tackle this issue, optical biosensing strategies have been incorporated into point-of-care (POC) systems, offering real-time monitoring, field-deployable, and low-cost devices, which help make on-the-spot decisions.This review aims to discuss the recent cutting-edge research on POC optical biosensing platforms for on-farm diagnosis of animal diseases and on-site detection of animal-derived food-borne contaminants, including pathogens, antibiotics, and mycotoxins. Moreover, this review briefly presents the basic knowledge of various types of optical biosensors and their development using various recent strategies, including nanomaterial combinations, to enhance their performance in POC tests.This review is expected to help scientists to understand the evolution and challenges in the development of point-of-care biosensors for the food and livestock industry, benefiting global healthcare.
Keywords: Optical biosensor; Food safety; Point-of-care; Livestock diseases; Zoonotic diagnostics; Nanomaterials; SURFACE-PLASMON RESONANCE; LATERAL-FLOW IMMUNOASSAY; MOUTH-DISEASE VIRUS; SENSITIVE DETECTION; LABEL-FREE; RAPID DETECTION; ANTIBIOTIC-RESIDUES; IMMUNOCHROMATOGRAPHIC ASSAY; DAIRY-COWS; QUANTITATIVE DETECTION; Pharmacology & Pharmacy